Culture Always Operates Through and in the Body: How Culture Constructs and Reshapes the Female Body (Asian Journal of Social Science Studies, 2022)
This article discusses the relationship between culture and the body, with a particular focus on the female body and the cultural construction of its biology by society. Culture always operates through and in the body, which is often embodied through the spheres of labour, production and reproduction, and is constantly reinforced in scientific knowledge and social common sense. This article is based on the literature research method to explain this view. The article explores the ways in which scientific knowledge and social practices perceive and shape women’s gender and bodies from different perspectives such as labour, production and reproduction, concluding that culture always constructs and operates on the female body. At the same time, the female body is not only culturally defined and interpreted, but also culturally and economically altered in a physical sense. Biological science and society’s traditional views on gender and the body are deeply entrenched and need to be changed in many ways, from the law, education, publicity and, most fundamentally, institutional and policy direction.